2021
DOI: 10.1007/s43452-021-00246-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of equal channel angular pressing and heat treatments on the microstructures and mechanical properties of selective laser melted and cast AlSi10Mg alloys

Abstract: This study investigated the impact of the equal channel angular pressing (ECAP) combined with heat treatments on the microstructure and mechanical properties of AlSi10Mg alloys fabricated via selective laser melting (SLM) and gravity casting. Special attention was directed towards determining the effect of post-fabrication heat treatments on the microstructural evolution of AlSi10Mg alloy fabricated using two different routes. Three initial alloy conditions were considered prior to ECAP deformation: (1) as-cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Taking into account the strengthening components, the increases in strength in the sample after two passes of ECAP can be expressed as follows: σ y = 72 f riction stress + 79 Orowan + 81.6 Hall−Petch + 186.7 dislocation = 419.3 MPa (7) According to Equation ( 7), the calculated yield strength of the AlSi10Mg alloy subjected to two passes of ECAP was equal to 419.3 MPa. This estimated value of YS was similar to the experimental value of 382 MPa obtained from the static compression test in our previous study [25].…”
Section: Analysis Of Strengthening Mechanisms Of the Ecap-processed S...supporting
confidence: 90%
See 3 more Smart Citations
“…Taking into account the strengthening components, the increases in strength in the sample after two passes of ECAP can be expressed as follows: σ y = 72 f riction stress + 79 Orowan + 81.6 Hall−Petch + 186.7 dislocation = 419.3 MPa (7) According to Equation ( 7), the calculated yield strength of the AlSi10Mg alloy subjected to two passes of ECAP was equal to 419.3 MPa. This estimated value of YS was similar to the experimental value of 382 MPa obtained from the static compression test in our previous study [25].…”
Section: Analysis Of Strengthening Mechanisms Of the Ecap-processed S...supporting
confidence: 90%
“…Meanwhile, it is only very recently that the microstructure and mechanical properties of SLM-fabricated and then ECAP-processed AlSi10Mg alloy were investigated by the current authors [25]. In this article, it was found that the yield strength increased significantly (up to 382 MPa).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…More details about the applied scanning strategy and SLM process parameters can be found in our previous studies [33,34].…”
mentioning
confidence: 99%